Penetrating neck injuries with laryngeal framework involvement: in a tertiary care centre - Periasamy, Chozhan; Ravisankar, Malarvizhi; Subburayalu, Mathumithaa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Penetrating neck injuries are very common as a mode of homicidal and suicidal injuries. Not many of them are deep enough to affect the laryngeal framework. Methods: Prospective study in the Department of ENT Stanley Medical College, Chennai. The study period was from January 2018 to December 2018. Follow up of 3 months was done. Results: Penetrating neck injuries treated on emergency care with tracheostomy and wound exploration and repair. It was found to be more common in young male population. Conclusions: Laryngeal framework involvement necessitates tracheostomy during wound exploration. On table laryngeal injury repair improves prognosis and early post-operative vocal fold assessment helps frame a treatment plan designed specifically for the patient.